Redesign and Simulation of Computer Networks in IoT-Based Medical Records Laboratory - Oki Setiono; Retno Astuti Setijaningsih; Wildanil Ghozi (Jurnal Mantik, 2022)
The medical record laboratory has a very important function, one of which is in serving patients using electronic medical records or often referred to as hospital management information systems. A computer network in a medical record laboratory in an educational institution is a very important infrastructure in carrying out learning activities, without exception on the computer network in the medical records laboratory at Dian Nuswantoro University. The current condition of the computer network still has shortcomings such as inappropriate network management, network devices that are not configured and features on the server that are less than optimal. The purpose of this research is to redesign and simulate computer networks with simulators to design a more optimal network and add network features that do not yet exist including the application of the internet of things (IoT) for maximum medical record laboratory services. The expected results of the redesign and simulation are that in order to run properly, there are changes to the design and needs of network devices that can be adjusted to the conditions they should be. Network devices that have been configured have DHCP server, NTP, FTP and Web server facilities. The addition of a motion sensor to turn on the laboratory room lights before use can also work well.